Способы создания комического эффекта в романе Апулея «Метаморфозы» - Захарова, Екатерина Анатольевна (Philologia Classica, 2007)
Brilliance of style in Apuleius’ «Metamorphoses» is based not only on the lexical abundance and on the variety of stylistic figures: it is humour that keeps parts of the romance together. On this point we should speak about different text levels. The fabula is evidently comic itself. The whole novel could be observed as a complex of parodies —a parody of Greek romance, epos, rhetoric (e.g. laudatio funebris) or even Greek tragedy. Then, some plotlines derived from so-called Milesian tales are highly amusing. The witty allusions to the Roman law (e.g. Venus and Psyche), comic situations, in which gods take part (e.g. Cupid on a cypress tree), and absurd statements made in a serious way (e.g. Lamachus buried in the sea that does not exist near Thebes) —all these means are efficient to produce comic effect. And the position of Lucius, asinus philosophans, —the ass being indignant about the world’s immorality —seems to be absolutely hilarious.